Potential for the Occurrence of Sedimentary Sulphur Deposits in Northeastern British Columbia - V. F. Hollister (Canadian Institute of Mining, Metallurgy and Petroleum, 1977)
Four conditions are commonly accepted as being needed for the development of native sulphur deposits in sedimentary rocks : (1) ample sulphate-bearing evaporite, normally anhydritic; (2) proximity to petroleum deposits; (3) a hydrodynamic system of communication between these two; (4) a stratigraphic or structural trap to prevent escape of the sulphur and sulphur -bearing reaction products. When any of these requisites are absent, apparently no significant residual bio-epigenetic sulphur deposit will form. These requirements are, however, satisfied in some areas, which include both the Triassic and Devonian evaporites of northeastern British Columbia.